Coquina. Images of Cooks in Contemporary Gastromania - Marrone, Gianfranco (E|C, 2025)
Can we be sure that modern chefs are all the same, with the same qualities, skills, knowledge and values? Can we assume that chefs everywhere adhere to the same systems of meaning and cooking procedures? Can we affirm that the surprise effect, so often sought after and criticised, and perhaps peppered with stereotypical values (sustainability, care for the environment, fighting waste, farm to fork, respect for tradition, the search for the absolute flavour, vegetarianism...) is the only goal of the contemporary cook? Or are we perhaps faced with a conceptual fog involving aesthetics, ethics, politics, society, the economy and religion that should be articulated and redefined in order to be better understood? This paper aims to answer such questions.